2013
DOI: 10.1371/journal.pgen.1003654
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus Promotes Recruitment and Degradation of Farnesylated Prickle in Drosophila melanogaster Planar Polarity Specification

Abstract: The core planar polarity proteins are required to specify the orientation of structures that are polarised in the plane of the epithelium. In the Drosophila melanogaster wing, the core proteins localise asymmetrically at either proximal or distal cell edges. Asymmetric localisation is thought to be biased by long-range cues, causing asymmetric complexes to become aligned with the tissue axes. Core proteins are then thought to participate in feedback interactions that are necessary to amplify asymmetry, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 49 publications
(64 reference statements)
8
78
1
Order By: Relevance
“…S4A-C). In light of previous evidence that Vang participates in the control of Pk protein levels (Strutt et al, 2013b), our results suggest that Vangl1 overexpression might be leading to increased levels of Pk2 degradation, which in turn leads to a reduction in Pk2 and to associated Dvl1 patterning defects.…”
Section: Role Of Pk2 In the Control Of Asymmetric Cortical Vangl1 Dynsupporting
confidence: 67%
“…S4A-C). In light of previous evidence that Vang participates in the control of Pk protein levels (Strutt et al, 2013b), our results suggest that Vangl1 overexpression might be leading to increased levels of Pk2 degradation, which in turn leads to a reduction in Pk2 and to associated Dvl1 patterning defects.…”
Section: Role Of Pk2 In the Control Of Asymmetric Cortical Vangl1 Dynsupporting
confidence: 67%
“…1C,D,E). Under similar conditions, Sple tagged with green fluorescent protein (GFP) localizes to the distal side of the cell, opposite to the proximal localization of Pk in wild-type wings (Strutt et al, 2013). This is indicative of reversal of the entire core complex, as confirmed here by the clonal expression of Vang::YFP (Fig.…”
Section: Pk-sple Isoform Expression Determines the Direction Of Hair supporting
confidence: 54%
“…Overexpressing Sple in wings produces varying degrees of polarity reversal (supplementary material Fig. S1) (Gubb et al, 1999;Lee and Adler, 2002;Doyle et al, 2008;Lin and Gubb, 2009;Strutt et al, 2013). Similar dependence on a single Pk-Sple isoform is seen for A-abd, P-abd and eye (Gubb et al, 1999;Lawrence et al, 2004), and ectopic expression of the alternative isoform has been observed to produce reversals of polarity in A-abd and P-abd (Lawrence et al, 2004).…”
Section: Pk-sple Isoform Expression Determines the Direction Of Hair mentioning
confidence: 79%
See 1 more Smart Citation
“…Fz, Dsh and Dgo concentrate on the one face of a cell, and Stbm and Prickle1 concentrate on the opposite; Fmi is present at both. Stbm is required for the recruitment of Prickle1 at proximal cell ends in the pupa wing and promotes the degradation of excess Prickle1 to maintain its asymmetrical localization (Strutt et al, 2013). Arf1 and adaptor protein-1 (AP-1) are required for the planar polarized enrichment of core PCP proteins along the proximaldistal axis (Carvajal-Gonzalez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%